Library Chat Transcript Evaluation for User Sentiment During the COVID-19 Pandemic - Kathryn Barrett; Ansh Sharma (Evidence Based Library and Information Practice)
Objective – The purpose of this research was to explore user sentiment on Ask a Librarian, a consortial chat service for university libraries in Ontario, Canada, between 2019 to 2021. We tested how the characteristics of the chat (such as year, semester, user type, operator type, affiliation mismatch, and user complaints) and the onset of the COVID-19 pandemic affected sentiment scores.